The anti-Candida activity by Ancillary Proteins of an Enterococcus faecium strain - Roy, Utpal; Chalasani, Ajay G.; Shekh, M. Raeesh (Frontiers in Microbiology, 2015)
An antimycotic activity toward seven strains of Candida albicans was demonstrated erstwhile by a wild-type Enterococcus faecium isolated from a penguin rookery of the Antarctic region. In the present study the antimicrobial principle was purified by ion exchange and gel permeation chromatography and further was analyzed by LC-ESI-MS/MS. In the purification steps, the dialyzed concentrate and ion exchange fractions inhibited C. albicans MTCC 3958, 183, and SC 5314. However, the gel filtration purified fractions inhibited MTCC 3958 and 183. The data obtained from the LC-ESI-MS/MS indicate that the antimicrobial activity of the anti-Candida protein produced by E. faecium is facilitated by Sag A/Bb for the binding of the indicator organism's cell membrane. Partial N-terminal sequence revealed 12 N-terminal amino acid residues and its analysis shown that it belongs to the LysM motif. The nucleotide sequence of PCR-amplified product could detect 574 nucleotides of the LysM gene responsible for binding to chitin of the cell wall of Candida sp.